Libya and the United States : two centuries of strife - St. John, Ronald Bruce (University of Pennsylvania Press, 2002)
"This is a wonderfully measured, insightful, comprehensive treatment of the subject that will, in my estimation, become a standard not only for the academic community but also for the policy and intelligence community."--Dirk Vandewalle, Dartmouth College.